APPLICATION OF THE MARKET PLACE LEARNING METHOD TO INCREASE STUDENTS' LEARNING MOTIVATION IN THE SUBJECTS OF PAI AND CIVIL CIVIL CLASS VIII OF AL-IKHLASHIYAH ISLAM SMP TIMUR - indah qurratul ain (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research was motivated by the low learning motivation of students in the PAI-BP class VIII B subject. Results: Pre-action student learning motivation in PAI-BP learning was generally classified as good, with an average score of 59.4% from 22 participants. students, 21 students are in the good category and 1 is in the sufficient category. An alternative solution to this problem is by applying new learning methods such as the Market Place method in PAI-BP learning. This research uses classroom action research. The subjects of this research were 22 students in class VIII B. Data was obtained through observation sheets, documentation and motivation questionnaires. The questionnaire used was in the form of multiple choices consisting of 22 statement items containing the choices always, often sometimes and never. The questionnaire was used in each cycle, namely in cycles I and II. The results of filling out the questionnaire in cycle I showed that 6 students had very good learning motivation, 15 in the good category, and 1 in the sufficient category with an average score of 66.6%. Cycle II saw an increase of 16 students in the very good category and 6 in the good category with an average score of 80.1%. The results of observations on students and teachers also showed an increase, in cycle I the student activity looked quite good, increasing to the very good category in cycle II, and the teacher activity in cycle I was good, increasing to the very very good category in cycle II.